Determinanty sukcesu zarządzania projektami informatycznymi w opiniach ekspertów - Witold Chmielarz; Anna Sołtysik-Piorunkiewicz (Studia i Materiały)
Purpose: The primary purpose of the article is to identify factors and activities influencing the proper management of IT projects. Method: The study was based on the opinions of forty-five experts who took part in the BPM Symposium organized in April 2023 at the University of Warsaw. Expert opinions were collected using a survey questionnaire based on literature analysis and our own professional experience in project management.